2017
DOI: 10.1038/srep40016
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Risks of Inapparent Avian Exposure for Human Infection: Avian Influenza Virus A (H7N9) in Zhejiang Province, China

Abstract: Inapparent avian exposure was suspected for the sporadic infection of avian influenza A(H7N9) occurring in China. This type of exposure is usually unnoticed and difficult to model and measure. Infected poultry with avian influenza H7N9 virus typically remains asymptomatic, which may facilitate infection through inapparent poultry/bird exposure, especially in a country with widespread practice of backyard poultry. The present study proposed a novel approach that integrated ecological and case-control methods to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…In addition, the current study demonstrated that the maleto-female ratio of patients was approximately 2.0:1, and this pattern is consistent with results of previous studies (Sun et al, 2014;Chen et al, 2013c). An explanation for these results is that Chinese men are more likely to engage in selling or slaughtering live poultry than women (Cowling et al, 2013); another explanation may be that most Asian males have birdrelated hobbies, and they probably visit LPMs frequently and keep pet birds at home (Ge et al, 2017); all aforementioned behaviors might have increased the potential of unapparent exposure to A (H7N9) infected avian and avian-related environment in males. Furthermore, this study demonstrated that the median age of patients with A (H7N9) infection was 56 (range, 1 to 88) years, most cases occurred in the 60-to 79year-old group, and the proportion of fatal cases was higher than nonfatal cases in patients more than 60 years old.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the current study demonstrated that the maleto-female ratio of patients was approximately 2.0:1, and this pattern is consistent with results of previous studies (Sun et al, 2014;Chen et al, 2013c). An explanation for these results is that Chinese men are more likely to engage in selling or slaughtering live poultry than women (Cowling et al, 2013); another explanation may be that most Asian males have birdrelated hobbies, and they probably visit LPMs frequently and keep pet birds at home (Ge et al, 2017); all aforementioned behaviors might have increased the potential of unapparent exposure to A (H7N9) infected avian and avian-related environment in males. Furthermore, this study demonstrated that the median age of patients with A (H7N9) infection was 56 (range, 1 to 88) years, most cases occurred in the 60-to 79year-old group, and the proportion of fatal cases was higher than nonfatal cases in patients more than 60 years old.…”
Section: Discussionmentioning
confidence: 99%
“…where D represents the environment factors; i  1, 2, All six comprehensive factors are continuous variables, and thus had to be stratified though discretization before they could be used in the GDM (Wang and Xu 2017, Wang and Xu 2017, Wang et al 2010, Ge et al 2017, Wang et al 2017a. In order to avoid subjectivity and randomness in the process of discretization, this study used the natural break classification method, which performs an automatic unsupervised segmentation of the comprehensive factors to receive the breakpoints between the segments (Xu and Zhang 2014).…”
Section: Geographical Detector Model (Gdm)mentioning
confidence: 99%
“…Reason for the distance determination: The Chinese population usually commutes 1 to 3 kilometers in their communities every day [35].…”
Section: Network Constructionmentioning
confidence: 99%